1996
DOI: 10.1128/iai.64.5.1666-1671.1996
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated vaccinia virus-circumsporozoite protein recombinants confer protection against rodent malaria

Abstract: NYVAC-based vaccinia virus recombinants expressing the circumsporozoite protein (CSP) were evaluated in the Plasmodium berghei rodent malaria model system. Immunization of mice with a NYVAC-based CSP recombinant elicited a high level of protection (60 to 100%). Protection did not correlate with CS repeat-specific antibody responses and was abrogated by in vivo CD8 ؉ T-cell depletion. Protection was not enhanced by modification of the subcellular localization of CSP. These results suggest the potential of poxvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Recombinant vaccinia viruses. Recombinant poxviruses were produced in collaboration with Virogenetics Corporation (Troy, N.Y.) (24,42 Immunization regimen. Fifteen malaria-naive rhesus monkeys (Macaca mulata), age 1 to 1.5 years and weighing 1.5 to 3 kg, were randomized into five groups of three monkeys per group (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant vaccinia viruses. Recombinant poxviruses were produced in collaboration with Virogenetics Corporation (Troy, N.Y.) (24,42 Immunization regimen. Fifteen malaria-naive rhesus monkeys (Macaca mulata), age 1 to 1.5 years and weighing 1.5 to 3 kg, were randomized into five groups of three monkeys per group (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…One rationale for developing a poxvirus-based vaccine was to maximize the elicitation of cellular immunity, particularly CTL responses (45). The inclusion of at least five antigens expressed during the liver stage of parasite development (25,66,77), and probably a sixth (AMA1), provides NYVAC-Pf7 with the potential to direct a broad-based CTL response against infected liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, these antigens have been shown to provide a level of protection in experimental models of malaria infection. CSP and SSP2 elicit protective immune responses, particularly cellular responses mediated by CD8 ϩ T cells (1,45,46,57,67,70,72), in rodents. Although CSPbased vaccine candidates evaluated in human clinical trials have provided disappointing results (2,30), the tested vaccines have in general been designed to elicit humoral rather than cellular responses.…”
Section: Fig 3 Cell Surface Expression Of P Falciparum Antigens Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts aimed at inducing protection in humans by using different CS protein-based vaccines have failed or resulted in incomplete protection (4,6,26,30). Plasmid DNA (3,15,18,20) and attenuated recombinant poxvirus vectors (2,23,35) are also being employed in the effort to generate effective malaria vaccines. The availability of gene transfer technology for the protozoan parasite Toxoplasma gondii may offer an additional opportunity to express and deliver the CS protein in a highly immunogenic form.…”
mentioning
confidence: 99%